2015
DOI: 10.3171/2014.10.jns132643
|View full text |Cite
|
Sign up to set email alerts
|

Subtemporal transtentorial approach for recurrent trigeminal neuralgia after microvascular decompression via the lateral suboccipital approach: case report

Abstract: Microvascular decompression (MVD) via lateral suboccipital craniotomy is the standard surgical intervention for trigeminal neuralgia (TN). For recurrent TN, difficulties are sometimes encountered when performing reoperation via the same approach because of adhesions and prosthetic materials used in the previous surgery. In the present case report the authors describe the efficacy of the subtemporal transtentorial approach for use in recurrent TN after MVD via the lateral suboccipital approach. An 86-year-old w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…These data hypothesize Otx2 is absolutely required for normal choroid plexus development; however its importance in the general maintenance in the mature/adult choroid plexus is yet to be ascertained. It is known however in humans the obliteration of the lateral ventricular choroid plexus as a treatment for hydrocephalus results in no regeneration of the structure (Hallaert et al, 2012; Ogiwara et al, 2014). This suggests early developmental growth factor patterning cues are paramount for normal plexus development, and the structure cannot regenerate from already-present plexus epithelium.…”
Section: Normal Developmentmentioning
confidence: 99%
“…These data hypothesize Otx2 is absolutely required for normal choroid plexus development; however its importance in the general maintenance in the mature/adult choroid plexus is yet to be ascertained. It is known however in humans the obliteration of the lateral ventricular choroid plexus as a treatment for hydrocephalus results in no regeneration of the structure (Hallaert et al, 2012; Ogiwara et al, 2014). This suggests early developmental growth factor patterning cues are paramount for normal plexus development, and the structure cannot regenerate from already-present plexus epithelium.…”
Section: Normal Developmentmentioning
confidence: 99%
“…A). This approach is often used if a retrosigmoid/suboccipital craniectomy is not optimal or if the MVD approach failed to provide pain relief . On the other hand, we found a decrease in the number of percutaneous rhizotomy procedures done to treat TN (Fig.…”
Section: Resultsmentioning
confidence: 82%
“…13 Recently Ogiwara et al, found it useful in cases of recurrent trigeminal neuralgia who were operated on with the standard retrosigmoid approach or when the offending vessel was distal to the root entry zone or on its anterolateral side. 11 In trigeminal schwannomas extending from the middle fossa through the porus trigeminus into the posterior fossa, the tumor medial to the internal acoustic canal can also be approached. 34…”
Section: Discussionmentioning
confidence: 99%
“…13 Recently Ogiwara et al, found it useful in cases of recurrent trigeminal neuralgia who were operated on with the standard retrosigmoid approach or when the offending vessel was distal to the root entry zone or on its anterolateral side. 11 In trigeminal schwannomas extending from the middle fossa through the porus trigeminus into the posterior fossa, the tumor medial to the internal acoustic canal can also be approached. 34 With respect to accessing the retroinfudibular/retrochiasmatic region, the location of the parasellar tumor in relation to the optic chiasm and to the pituitary stalk has to be taken into consideration during selection of the surgical approach.…”
Section: Indications For These Approachesmentioning
confidence: 99%
See 1 more Smart Citation